International Trade and Job Polarization: Evidence at the Worker Level - Wolfgang Keller; Hale Utar (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the role of international trade for job polarization, the phenomenon in which employment for high- and low-wage occupations increases but mid-wage occupations decline. With employer-employee matched data on virtually all workers and firms in Denmark between 1999 and 2009, we use instrumental-variables techniques and a quasi-natural experiment to show that import competition is a major cause of job polarization. Import competition with China accounts for about 17% of the aggregate decline in mid-wage employment. Many mid-skill workers are pushed into low-wage service jobs while others move into high-wage jobs. The direction of movement, up or down, turns on the skill focus of workers' education. Workers with vocational training for a service occupation can avoid moving into low-wage service jobs, and among them workers with information-technology education are far more likely to move into high-wage jobs than other workers.
Keywords: 330; import competition; inequality; vocational training